Uniqueness of L-functions and general meromorphic functions in light of two shared sets - Saha, R.; Mallick, S. (Հայաստանի ԳԱԱ)
In this paper, we have dealt with the uniqueness problem of a general meromorphic function with L function in terms of two shared sets. In our main theorem, we deal with general meromorphic functions instead of meromorphic functions having finitely many poles. As a corollary of our main theorem, we have shown that our result not only fills the gap of some theorems of [3] and [1] for m = n − 1 but also reduces the cardinality of the main range set and hence our result significantly improves all the results in this direction.
Keywords: Mathematics